Adaptaciones hematológicas de los Camélidos Sudamericanos que viven en zonas de elevadas altitudes - Quispe Peña, Edgar (Revista Complutense de Ciencias Veterinarias, 2011)
The South American camelids (SAC) did not always live in high altitude areas. Diverse researchers have demonstrated that a great amount of camelids lived in the coast in the pre-Columbian era. At present times, raising of alpaca, llama and vicuña is carried out mainly at high altitude, associated with the diminution of concentration of oxygen, temperature and humidity, as well as with the increase of cosmic radiations. SAC have adapted to these conditions by biological, morphologic and behaviour mechanisms that allow them to live in such an unfavorable environment. This review focuses mainly on the hypobaric hypoxia as a stress factor and the morphologic and physiological (haematological and circulatory) adaptations which the organism of SAC has had to modify to confront the diminished oxygen concentration.
Keywords: SAC; Adaptability; Hypoxia; Red blood cells; Haemoglobin; Oxygen